Pt and Pd co-doped In2O3 / TiO2 resistance type hydrogen sensor

By co-doping the In2O3/TiO2 composite material of Pt and Pd, PtPd@In2O3/TiO2 composite material for hydrogen sensing was prepared, which solved the problems of poor selectivity and low sensitivity of existing hydrogen sensors at room temperature, and achieved rapid and safe detection of hydrogen at room temperature.

CN119827585AActive Publication Date: 2025-04-15YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411962199.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing hydrogen sensors have poor selectivity, low sensitivity, and high operating temperatures, which can cause explosion risk, making it difficult to effectively detect hydrogen at room temperature.

Method used

The gas-sensitive performance of In2O3/TiO2 composite material is improved by co-doping of Pt and Pd, and PtPd@In2O3/TiO2 composite material is prepared as the gas-sensitive layer of the resistive hydrogen sensor to achieve rapid detection of hydrogen at room temperature.

Benefits of technology

It achieves rapid response and good selectivity to 2000ppm H2 at room temperature, with a response time of 29s and a recovery time of 41s, which significantly improves the sensitivity and safety of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827585A_ABST
    Figure CN119827585A_ABST
Patent Text Reader

Abstract

The invention discloses a Pt and Pd co-doped In2O3 / TiO2 resistance type hydrogen sensor. The Pt and Pd co-doped In2O3 / TiO2 resistance type hydrogen sensor consists of an Al2O3 ceramic substrate, an interdigital Au electrode coated on the surface of the Al2O3 ceramic substrate, and a gas sensitive film coated on the surface of the interdigital Au electrode, the gas sensitive film is prepared from a PtPd-coated In2O3 / TiO2 composite material, and the In2O3 / TiO2 material is prepared by taking absolute ethyl alcohol, anhydrous acetic acid, formamide, tetrabutyl titanate and indium chloride as raw materials through a supercritical drying method and a hydrothermal method. The gas-sensitive property of the In2O3 / TiO2 composite material is improved through co-doping of Pt and Pd, when the In2O3 / TiO2 composite material is used as a gas sensor, the maximum response of the hydrogen sensor to 2000 ppm H2 under the room temperature condition is 20.7566, the response time is 29 s, the recovery time is 41 s, and good selectivity is achieved. Therefore, the Pt and Pd co-doped In2O3 / TiO2 resistance type hydrogen sensor prepared in the invention has the potential to become an excellent room temperature hydrogen sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation and application of hydrogen sensing materials, and in particular relates to a Pt and Pd co-doped In2O3 / TiO2 resistance type hydrogen sensor, a preparation method and application thereof. Background Art

[0002] Hydrogen is colorless and odorless, has high combustion energy and is green, and is considered a promising alternative to fossil fuel energy in the future. In addition, hydrogen can meet applications in power generation, scientific research, methanol industry, petroleum, nuclear power plants, fertilizer plants, and other fields. However, the diffusion coefficient of hydrogen is about 12 times that of natural gas or gasoline, its flame propagation speed is large and the explosion concentration range is wide. Due to its volatility and high flammability, the storage and transportation of hydrogen are the focus of attention. For safety reasons, high-quality gas sensors are essential for the safe storage, detection, and monitoring of hydrogen. Hydrogen sensors with higher selectivity and high response range can prevent various safety hazards. However, it should be able to function at the lowest possible temperature to minimize the risk of hydrogen explosion, so it is necessary to develop a hydrogen sensor that works at room temperature to detect hydrogen.

[0003] Among many gas sensors, metal oxide (TiO2, In2O3, SnO2, ZnO, etc.) resistive hydrogen sensors have been widely studied at this stage, but they still have unsatisfactory shortcomings such as insufficient response and poor stability. Even at lower operating temperatures, they have poor selectivity and very low sensitivity.

[0004] Yasuhisa Naitoh et al. (Sens. Actuators B Chem 2020 321 128525) prepared TiO2 nanotubes by anodization. The hollow nanoscale tube wall provided a huge specific surface area, and used atomic layer deposition technology to decorate the TiO2 nanotube film with precious metal (Pt) nanoparticles. The device operated at a temperature of 300°C. The study found that in the medium concentration region, gas molecules gradually diffused into the nanocavities. Adsorption and gas diffusion on the inner wall surface of the nanopore occurred simultaneously, and the response deviated from the proportional relationship with the gas concentration, and the linear relationship of the response was poor.

[0005] Sui et al. (Int. J. Hydrogen Energy 2024 55 855-863) prepared a TiO2 aerogel skeleton hydrogen sensor decorated with Pd nanoparticles. The aerogel structure has a large specific surface area and high porosity, but the device operates at a temperature of 325°C, which leads to safety risks when detecting hydrogen.

[0006] In the patent application with application number 202410577281, a heterojunction In2O3 / TiO2 composite material is obtained by sol-gel method. The composite material has a porous structure, fast response / recovery time and high linearity, and has good stability in multiple cycles. However, when it is used as a gas sensor, the high operating temperature poses an explosion risk when detecting hydrogen leakage. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a Pt, Pd co-doped In2O3 / TiO2 resistive hydrogen sensor. The present invention improves the gas sensitive performance of the In2O3 / TiO2 composite material by co-doping with Pt and Pd. When it is used as a gas sensor, the response time is shorter and has good selectivity.

[0008] The objective of the present invention is achieved through the following technical scheme: a Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor is composed of an Al2O3 ceramic substrate, an interdigitated Au electrode coated on the surface of the Al2O3 ceramic substrate, and a gas sensitive film coated on the surface of the interdigitated Au electrode; the gas sensitive film is made of a PtPd@In2O3 / TiO2 composite material, and the PtPd@In2O3 / TiO2 composite material is prepared by the following steps:

[0009] (1) adding anhydrous acetic acid and tetrabutyl titanate into anhydrous ethanol and stirring to uniformly mix the mixture into a solution A containing anhydrous acetic acid and tetrabutyl titanate, wherein the volume ratio of anhydrous acetic acid, tetrabutyl titanate and anhydrous ethanol is 2-10:15-20:20-50;

[0010] Add anhydrous acetic acid, deionized water and formamide into anhydrous ethanol and stir to mix them evenly to form a solution B containing anhydrous acetic acid, deionized water and formamide, wherein the volume ratio of anhydrous acetic acid, deionized water, formamide and anhydrous ethanol is 2-10:1-5:0.1-2:10-20;

[0011] (2) adding solution B to solution A and stirring to obtain a gel precursor solution after uniform stirring, and placing the gel precursor solution in a thermostat to obtain a wet gel; subjecting the wet gel to solvent exchange aging, soaking the wet gel in ethanol, and obtaining a block TiO2 aerogel after supercritical drying;

[0012] (3) adding indium nitrate and dilute hydrochloric acid solution to deionized water and stirring, wherein the ratio of the mass of indium nitrate to the volume of dilute hydrochloric acid and the volume of deionized water is 0.1-1:1-10:10-20; adding block TiO2 aerogel to ammonia water and stirring, wherein the ratio of the mass of block TiO2 aerogel to the volume of ammonia water is 0.5-3:5-10; then mixing the two solutions, transferring the mixed solution to a reactor for hydrothermal treatment, centrifuging the white precipitate, washing with ethanol, and drying to obtain a white powder;

[0013] (4) putting the white powder in step (3) into a porcelain boat, placing the porcelain boat in a tube furnace, calcining in an air atmosphere, and collecting a light yellow In2O3 / TiO2 powder;

[0014] (5) adding light yellow In2O3 / TiO2 powder to deionized water, stirring with ultrasound, and collecting to obtain In2O3 / TiO2 dispersion A, wherein the ratio of the mass of the light yellow In2O3 / TiO2 powder to the volume of deionized water is 0.1-5:10-30;

[0015] Weigh chloroplatinic acid, palladium chloride and dilute hydrochloric acid, add them into deionized water, and ultrasonically stir at room temperature to obtain an orange-yellow liquid B; the ratio of the mass of chloroplatinic acid, the mass of palladium chloride, the volume of dilute hydrochloric acid and the volume of deionized water is 0.5-5:0.5-5:2-10:10-20;

[0016] Add L-ascorbic acid to deionized water to prepare a transparent solution C; the ratio between the mass of L-ascorbic acid and the volume of deionized water is 0.176-0.528:10-30;

[0017] (6) adding the orange-yellow liquid B and the transparent solution C obtained in (5) to the dispersion A in sequence to obtain an orange-yellow mixed liquid, stirring and aging at room temperature to obtain a PtPd@In2O3 / TiO2 mixed liquid;

[0018] (7) The black precipitate obtained by centrifuging the PtPd@In2O3 / TiO2 mixed solution is washed with deionized water for multiple times and dried in an oven to obtain a first material; the first material is placed in a porcelain boat, the porcelain boat is placed in a tubular furnace, and calcined in an air atmosphere, and the black powder of the PtPd@In2O3 / TiO2 composite is collected to obtain a second material, namely, a PtPd@In2O3 / TiO2 composite material.

[0019] In the step (3), the hydrothermal treatment is specifically: hydrothermal treatment at 120-150° C. for 10-12 hours; in the steps (3) and (7), the drying is specifically: drying at 60-80° C. for 12-24 hours.

[0020] The length of the Al2O3 ceramic substrate is 18-25mm, and the width is 5-10mm; the length of the interdigitated Au electrode is 8-10mm, and the width is 4-6mm, and the line width is 45-50μm; the thickness of the gas sensitive film is 150-200μm.

[0021] Another object of the present invention is to provide a method for preparing a resistive hydrogen sensor of a Pt and Pd co-doped In2O3 / TiO2 composite material, which is prepared using the above materials, and the specific preparation steps are as follows:

[0022] (1) mixing the PtPd@In2O3 / TiO2 composite material with anhydrous ethanol in a mass ratio of 2 to 8:1, and grinding the mixture into a paste slurry; and coating the slurry on the surface of the interdigitated Au electrode;

[0023] (2) The device obtained in (1) is aged at 200-350° C. for 4-12 h to obtain a resistive hydrogen sensor of Pt and Pd co-doped In2O3 / TiO2 composite material.

[0024] The resistance-type hydrogen sensor of the Pt and Pd co-doped In2O3 / TiO2 composite material of the present invention is applied to hydrogen detection.

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention realizes rapid detection of hydrogen at room temperature through the electronic sensitization effect of Pt and Pd and the nn heterojunction formed between TiO2 and In2O3, thereby solving the safety problem of existing hydrogen-sensitive materials caused by excessively high operating temperatures.

[0027] (2) The present invention improves the gas-sensing performance of the In2O3 / TiO2 composite material by co-doping with Pt and Pd. When used as a gas sensor, the maximum response of the hydrogen sensor to 2000ppm H2 at room temperature is 20.7566, the response time is 29s, the recovery time is 41s, and the selectivity is good. Therefore, the Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor prepared in the present invention has the potential to become an excellent room temperature hydrogen sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The dynamic response curve of the composite material of this embodiment and the control group to 100-2000ppmH2 at room temperature;

[0029] Figure 2 5 cycles of 500 ppm hydrogen at room temperature in Example 3;

[0030] Figure 3 The selectivity of the composite materials of this example and the control group to various gases. DETAILED DESCRIPTION

[0031] The present invention provides a resistance-type gas sensor for hydrogen detection, comprising an electrode sheet and a gas-sensitive layer attached to the electrode sheet; the gas-sensitive layer is made of PtPd@In2O3 / TiO2 material, and the In2O3 / TiO2 material is prepared by supercritical drying and hydrothermal methods using anhydrous ethanol, anhydrous acetic acid, formamide, tetrabutyl titanate, and indium chloride as raw materials. The technical solution of the present invention is further described below.

[0032] The Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor provided by the present invention comprises an Al2O3 ceramic substrate, an interdigitated Au electrode coated on the surface of the Al2O3 ceramic substrate, and a gas sensitive film coated on the surface of the interdigitated Au electrode; the gas sensitive film is made of a PtPd@In2O3 / TiO2 composite material, and the PtPd@In2O3 / TiO2 composite material is prepared by the following steps:

[0033] (1) adding anhydrous acetic acid and tetrabutyl titanate into anhydrous ethanol and stirring to uniformly mix the mixture into a solution A containing anhydrous acetic acid and tetrabutyl titanate, wherein the volume ratio of anhydrous acetic acid, tetrabutyl titanate and anhydrous ethanol is 2-10:15-20:20-50;

[0034] Add anhydrous acetic acid, deionized water and formamide into anhydrous ethanol and stir to mix them evenly to form a solution B containing anhydrous acetic acid, deionized water and formamide, wherein the volume ratio of anhydrous acetic acid, deionized water, formamide and anhydrous ethanol is 2-10:1-5:0.1-2:10-20;

[0035] (2) adding solution B to solution A and stirring to obtain a gel precursor solution after uniform stirring, and placing the gel precursor solution in a thermostat to obtain a wet gel; subjecting the wet gel to solvent exchange aging, soaking the wet gel in ethanol, and obtaining a block TiO2 aerogel after supercritical drying;

[0036] (3) Indium nitrate and dilute hydrochloric acid solution are added to deionized water and stirred, and the ratio between the mass of indium nitrate, the volume of dilute hydrochloric acid and the volume of deionized water is 0.1-1:1-10:10-20; block TiO2 aerogel is added to ammonia water and stirred, and the ratio between the mass of block TiO2 aerogel and the volume of ammonia water is 0.5-3:5-10; then the two solutions are mixed, and the mixed solution is transferred to a reactor for hydrothermal treatment, and the white precipitate is centrifuged, washed with ethanol, and dried to obtain a white powder; the hydrothermal treatment is specifically: hydrothermal treatment at 120-150°C for 10-12h. The drying is specifically: drying at 60-80°C for 12-24h.

[0037] (4) The white powder in step (3) is placed in a porcelain boat, the porcelain boat is placed in a tube furnace, and calcined in an air atmosphere to collect a light yellow In2O3 / TiO2 powder; the calcination is specifically: calcined at 400-600°C for 2-5h.

[0038] (5) adding light yellow In2O3 / TiO2 powder to deionized water, stirring ultrasonically for 10 to 20 minutes, collecting and obtaining In2O3 / TiO2 dispersion A, wherein the ratio of the mass of the light yellow In2O3 / TiO2 powder to the volume of deionized water is 0.1 to 5:10 to 30;

[0039] Weigh chloroplatinic acid, palladium chloride and dilute hydrochloric acid, add them into deionized water, and ultrasonically stir for 10 to 20 minutes at room temperature to obtain an orange-yellow liquid B; the ratio of the mass of chloroplatinic acid, the mass of palladium chloride, the volume of dilute hydrochloric acid and the volume of deionized water is 0.5 to 5: 0.5 to 5: 2 to 10: 10 to 20;

[0040] Add L-ascorbic acid to deionized water to prepare a transparent solution C; the ratio between the mass of L-ascorbic acid and the volume of deionized water is 0.176-0.528:10-30;

[0041] (6) adding the orange-yellow liquid B and the transparent solution C obtained in (5) to the dispersion A in sequence to obtain an orange-yellow mixed liquid, stirring and aging at room temperature to obtain a PtPd@In2O3 / TiO2 mixed liquid;

[0042] (7) The black precipitate obtained by centrifuging the PtPd@In2O3 / TiO2 mixed solution is washed with deionized water for multiple times, and then dried in an oven to obtain a first material. The drying step is as follows: drying at 60 to 80°C for 12 to 24 hours; the first material is placed in a porcelain boat, and the porcelain boat is placed in a tube furnace, calcined in an air atmosphere, and a black powder of the PtPd@In2O3 / TiO2 composite is collected.

[0043] The second material is obtained, namely, the PtPd@In2O3 / TiO2 composite material. The calcination is specifically: calcining at 260-280°C for 2-4h.

[0044] The length of the Al2O3 ceramic substrate is 18-25mm, and the width is 5-10mm; the length of the interdigitated Au electrode is 8-10mm, and the width is 4-6mm, and the line width is 45-50μm; the thickness of the gas sensitive film is 150-200μm.

[0045] The present invention also provides a method for preparing a resistive hydrogen sensor of a Pt and Pd co-doped In2O3 / TiO2 composite material, which is prepared using the above materials, and the specific preparation steps are as follows:

[0046] (1) mixing the PtPd@In2O3 / TiO2 composite material with anhydrous ethanol in a mass ratio of 2 to 8:1, and grinding the mixture into a paste slurry; and coating the slurry on the surface of the interdigitated Au electrode (i.e., the Au-coated alumina electrode);

[0047] (2) The device obtained in (1) is aged at 200-350° C. for 4-12 h to obtain a resistive hydrogen sensor of Pt and Pd co-doped In2O3 / TiO2 composite material.

[0048] The resistance-type hydrogen sensor of the Pt and Pd co-doped In2O3 / TiO2 composite material of the present invention is applied to hydrogen detection.

[0049] The effect of the resistive gas sensor of the present invention is further verified below through specific examples, control groups and drawings.

[0050] Embodiment 1:

[0051] This embodiment provides a Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor, and the specific preparation steps are as follows:

[0052] (1) Preparation of nano-In2O3 / TiO2:

[0053] S1. Weigh 10 ml of anhydrous ethanol, 2 ml of anhydrous acetic acid, and 10 ml of tetrabutyl titanate, put them into a beaker and stir to mix them evenly to form solution A; weigh 10 ml of anhydrous ethanol, 2 ml of anhydrous acetic acid, 1 ml of deionized water, and 0.1 ml of DMF, put them into a beaker and stir to mix them evenly to form solution B; add solution B into solution A and stir, and after stirring evenly, let the obtained gel precursor solution stand in a thermostat; after solvent exchange aging of the wet gel, soak the wet gel with ethanol, and obtain block TiO2 aerogel by supercritical drying;

[0054] S2. Soak the wet gel in ethanol, replace it every 6-10 hours, and continue for more than 4 times to obtain the In2O3 / TiO2 composite precursor; Preparation: Weigh 0.5g indium nitrate, 20ml deionized water, 5ml dilute hydrochloric acid solution and 10ml ammonia water into a beaker and stir, mix evenly to obtain a mixed solution, take the block TiO2 aerogel and add it to the mixed solution. Transfer the mixed solution to the reactor for hydrothermal reaction, cool to room temperature, wash with deionized water, and dry to obtain a white powder.

[0055] S3. Weigh the white powder in step S2 and put it into a porcelain boat. Place the porcelain boat in a tube furnace, calcine it in an air atmosphere, and collect the light yellow In2O3 / TiO2 powder after natural cooling.

[0056] (2) Preparation of Pt0Pd1@In2O3 / TiO2:

[0057] S1. Weigh 200 mg of In2O3 / TiO2 powder into a beaker, add an appropriate amount of deionized water, stir ultrasonically for 10 minutes, and collect the In2O3 / TiO2 dispersion A.

[0058] S2. Weigh 1 mg of chloroplatinic acid, 1 mg of palladium chloride, 10 ml of deionized water, and 5 ml of 0.01 mol / L dilute hydrochloric acid, and stir them ultrasonically at room temperature for 20 min to mix them evenly to obtain an orange-yellow liquid B;

[0059] S3. Weigh 0.5 g L-ascorbic acid and 30 ml deionized water, stir at room temperature for 10 min to mix them evenly, and prepare a transparent solution C.

[0060] S4. Add solution B dropwise into dispersion A, stir at room temperature to mix evenly, and obtain an orange-yellow mixed liquid; add solution C dropwise into the mixed liquid, the color of the mixed liquid immediately changes to gray-brown, stir and age at room temperature for 22 hours to obtain a PtPd@In2O3 / TiO2 precursor solution.

[0061] S5. The black precipitate obtained by centrifugation of the aged precursor solution was washed with deionized water for multiple times and dried in an oven at 80°C to obtain the first material. The first material was placed in a porcelain boat, which was placed in a tube furnace and calcined at 350°C in an air atmosphere for 3 hours. After natural cooling, Pt0Pd1@In2O3 / TiO2 powder was collected. In the powder, the mass ratio of Pt compound to In2O3 / TiO2 was 1 / 98, and the mass ratio of Pd compound to In2O3 / TiO2 was 1 / 98, respectively.

[0062] Example 2: This example provides a Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor, which is different from Example 1 only in that the ratio of chloroplatinic acid, palladium chloride, deionized water, and 0.01 mol / L dilute hydrochloric acid in step (2) is 2 mg: 1 mg: 10 ml: 5 ml; in the powder, the mass ratio of Pt compound to In2O3 / TiO2 is 2 / 97, and the mass ratio of Pd compound to In2O3 / TiO2 is 1 / 97. The rest of the steps remain the same.

[0063] Example 3: This example provides a Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor, which is different from Example 1 only in that the ratio of chloroplatinic acid, palladium chloride, deionized water, and 0.01 mol / L dilute hydrochloric acid in step (2) is 1 mg: 2 mg: 10 ml: 5 ml; in the powder, the mass ratio of Pt compound to In2O3 / TiO2 is 1 / 97, and the mass ratio of Pd compound to In2O3 / TiO2 is 2 / 97. The rest of the steps remain the same.

[0064] Control group 1: a resistive hydrogen sensor, which is different from Example 1 only in that the ratio of chloroplatinic acid, palladium chloride, deionized water, and 0.01 mol / L dilute hydrochloric acid is 0 mg: 1 mg: 10 ml: 5 ml; in the black powder, the mass ratio of Pd compound to In2O3 / TiO2 is 1 / 99, respectively. The rest of the steps remain the same.

[0065] Control group 2: a resistive hydrogen sensor, which differs from Example 1 only in that in step (2), the ratio of chloroplatinic acid, palladium chloride, deionized water, and 0.01 mol / L dilute hydrochloric acid is 1 mg: 0 mg: 10 ml: 5 ml; in the powder, the mass ratio of Pt compound to In2O3 / TiO2 is 1 / 99, respectively. The rest of the steps remain the same.

[0066] The gas-sensitive performance test method for hydrogen is as follows:

[0067] Take 5 mg of the prepared light yellow powder and grind it with ethanol to form a uniform paste. Then apply the obtained slurry on the surface of the interdigital electrode (i.e., Au-coated alumina electrode) to form a thin layer in order to improve the stability of the sensing layer. First, introduce high-purity air until the resistance value of the test electrode stabilizes to Ra, and then introduce a specific concentration of target gas (mixed H2) until the resistance value drops to a stable value to obtain Rg. The response value is Ra / Rg. The larger the ratio, the greater the decrease in the resistance value of the electrode in hydrogen. Use a multi-channel tester with dynamic airflow to measure its hydrogen sensing performance, test the dynamic response curve of 100ppm to 2000ppm hydrogen, and the dynamic response-recovery curve; test its cyclic response to 500ppm hydrogen; test the selectivity to ethanol, methanol, ammonia, propylene glycol, and hydrogen.

[0068] Figure 1 The following are the dynamic response curves of the composite materials of the embodiment and the control group to 100-2000ppm H2 at room temperature. The following points can be known from the dynamic response curves and the curves of the response value changing with the concentration:

[0069] (1) The resistance of the PtPd@In2O3 / TiO2 sensor decreases after hydrogen is introduced, and increases after air is introduced, indicating that its response to hydrogen at room temperature is an n-type response.

[0070] (2) After 2000 ppm of hydrogen was introduced into the sensor of Example 3 (Pt1Pd2@In2O3 / TiO2), the maximum response value was 20.7566, the response time was 29 s, and the recovery time was 41 s, indicating that it had a good response to hydrogen at room temperature.

[0071] (3) The response of Example 3 (Pt1Pd2@In2O3 / TiO2) to 500 ppm hydrogen is 6.11, which is 5.41 times the response value (1.13) of Example 1 (Pt0Pd1@In2O3 / TiO2).

[0072] Figure 2 For Pt1Pd2@In2O3 / TiO2 (Example 3) at room temperature for 5 cycles of 500ppm hydrogen, Figure 2 It can be seen that the material has good repeatability and is also stable at room temperature.

[0073] Figure 3 The selectivity of the embodiments and the control group to various gases is given by Figure 3 The response values ​​of Example 3 (Pt1Pd2@In2O3 / TiO2) to 500 ppm gas are: hydrogen (6.11), ethanol (1.08), ammonia (1.33), propylene glycol (1.43), and methanol (1.076). Example 3 has good selectivity for hydrogen.

[0074] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A Pt and Pd co-doped In2O3 / TiO2 resistive hydrogen sensor, comprising an Al2O3 ceramic substrate, an interdigitated Au electrode coated on the surface of the Al2O3 ceramic substrate, and a gas sensitive film coated on the surface of the interdigitated Au electrode; characterized in that: The gas sensitive film is made of a PtPd@In2O3 / TiO2 composite material, and the PtPd@In2O3 / TiO2 composite material is prepared by the following steps: (1) adding anhydrous acetic acid and tetrabutyl titanate into anhydrous ethanol and stirring to uniformly mix the mixture into a solution A containing anhydrous acetic acid and tetrabutyl titanate, wherein the volume ratio of anhydrous acetic acid, tetrabutyl titanate and anhydrous ethanol is 2-10:15-20:20-50; Add anhydrous acetic acid, deionized water and formamide into anhydrous ethanol and stir to mix them evenly to form a solution B containing anhydrous acetic acid, deionized water and formamide, wherein the volume ratio of anhydrous acetic acid, deionized water, formamide and anhydrous ethanol is 2-10:1-5:0.1-2:10-20; (2) adding solution B to solution A and stirring to obtain a gel precursor solution after uniform stirring, and placing the gel precursor solution in a thermostat to obtain a wet gel; After the wet gel was subjected to solvent exchange aging, it was soaked in ethanol and supercritically dried to obtain block TiO2 aerogel; (3) adding indium nitrate and dilute hydrochloric acid solution to deionized water and stirring, wherein the ratio of the mass of indium nitrate to the volume of dilute hydrochloric acid and the volume of deionized water is 0.1-1:1-10:10-20; adding block TiO2 aerogel to ammonia water and stirring, wherein the ratio of the mass of block TiO2 aerogel to the volume of ammonia water is 0.5-3:5-10; then mixing the two solutions, transferring the mixed solution to a reactor for hydrothermal treatment, centrifuging the white precipitate, washing with ethanol, and drying to obtain a white powder; (4) putting the white powder in step (3) into a porcelain boat, placing the porcelain boat in a tube furnace, calcining in an air atmosphere, and collecting a light yellow In2O3 / TiO2 powder; (5) adding light yellow In2O3 / TiO2 powder to deionized water, stirring with ultrasound, and collecting to obtain In2O3 / TiO2 dispersion A, wherein the ratio of the mass of the light yellow In2O3 / TiO2 powder to the volume of deionized water is 0.1-5:10-30; Weigh chloroplatinic acid, palladium chloride and dilute hydrochloric acid, add them into deionized water, and ultrasonically stir at room temperature to obtain an orange-yellow liquid B; the ratio of the mass of chloroplatinic acid, the mass of palladium chloride, the volume of dilute hydrochloric acid and the volume of deionized water is 0.5-5:0.5-5:2-10:10-20; Add L-ascorbic acid to deionized water to prepare a transparent solution C; the ratio between the mass of L-ascorbic acid and the volume of deionized water is 0.176-0.528:10-30; (6) adding the orange-yellow liquid B and the transparent solution C obtained in (5) to the dispersion A in sequence to obtain an orange-yellow mixed liquid, stirring and aging at room temperature to obtain a PtPd@In2O3 / TiO2 mixed liquid; (7) The black precipitate obtained by centrifuging the PtPd@In2O3 / TiO2 mixed solution is washed with deionized water for multiple times and dried in an oven to obtain a first material; the first material is placed in a porcelain boat, the porcelain boat is placed in a tubular furnace, and calcined in an air atmosphere, and the black powder of the PtPd@In2O3 / TiO2 composite is collected to obtain a second material, namely, a PtPd@In2O3 / TiO2 composite material.

2. The resistive hydrogen sensor of the Pt and Pd co-doped In2O3 / TiO2 composite material as claimed in claim 1, characterized in that: In the step (3), the hydrothermal treatment is specifically: hydrothermal treatment at 120-150° C. for 10-12 hours; in the steps (3) and (7), the drying is specifically: drying at 60-80° C. for 12-24 hours.

3. The resistive hydrogen sensor of the Pt and Pd co-doped In2O3 / TiO2 composite material as claimed in claim 1, characterized in that: The calcination in step (4) is specifically carried out at 400-600°C for 2-5h; and in step (7), the calcination is specifically carried out at 260-280°C for 2-4h.

4. The resistive hydrogen sensor of the Pt and Pd co-doped In2O3 / TiO2 composite material as claimed in claim 1, characterized in that: The length of the Al2O3 ceramic substrate is 18-25mm, and the width is 5-10mm; the length of the interdigitated Au electrode is 8-10mm, and the width is 4-6mm, and the line width is 45-50μm; the thickness of the gas sensitive film is 150-200μm.

5. A method for preparing a resistive hydrogen sensor of a Pt and Pd co-doped In2O3 / TiO2 composite material, prepared by using the material according to any one of claims 1 to 4, and the specific preparation steps are as follows: (1) mixing the PtPd@In2O3 / TiO2 composite material with anhydrous ethanol in a mass ratio of 2 to 8:1, and grinding the mixture into a paste slurry; and coating the slurry on the surface of the interdigitated Au electrode; (2) The device obtained in (1) is aged at 200-350° C. for 4-12 h to obtain a resistive hydrogen sensor of Pt and Pd co-doped In2O3 / TiO2 composite material.

6. A resistive hydrogen sensor of a Pt and Pd co-doped In2O3 / TiO2 composite material as claimed in any one of claims 1 to 4, used in hydrogen detection.

Citation Information

Patent Citations

  • Ethyl acetate gas sensor and preparation method thereof

    CN106546637A

  • Hydrogen sulfide gas detection method based on nanosheet composite membrane and sensor

    CN111693579A

  • Titanium dioxide gas sensor and preparation method thereof

    CN115060766A

  • Preparation method of gas-sensitive material, product of gas-sensitive material and application of gas-sensitive material in hydrogen sensor

    CN119044252A

  • In2O3 composite TiO2 aerogel hydrogen-sensitive material and preparation method thereof

    CN119080052A